2000
DOI: 10.1111/j.1475-682x.2000.tb00895.x
|View full text |Cite
|
Sign up to set email alerts
|

Another Look at Classic Strain Theory: Poverty Status, Perceived Blocked Opportunity, and Gang Membership as Predictors of Adolescent Violent Behavior

Abstract: An extensive amount of criminological research has focused on the relationship between the inability of adolescents to achieve financial success or middle‐class status through legitimate channels and their subsequent involvement in delinquency. This genre of research is commonly recognized as structural‐strain theory. As the efficacy of this theory has periodically been questioned, this study addresses some of the methodological and theoretical issues associated with structural‐strain theory. Using a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…On other hand, the fact that this school-level effect is diminished with the addition of SES means that SES may strongly influence expectation and achievement within the school. It suggests that low economic status notably hinders both aspirations and outcomes, akin to the block opportunities framework where economic structures prevent higher personal attainment (Kao & Tienda, 1998; Vowell & May, 2000). In this discussion, I explain more how both the protective and restrictive factors operate in collective expectations.…”
Section: Discussionmentioning
confidence: 99%
“…On other hand, the fact that this school-level effect is diminished with the addition of SES means that SES may strongly influence expectation and achievement within the school. It suggests that low economic status notably hinders both aspirations and outcomes, akin to the block opportunities framework where economic structures prevent higher personal attainment (Kao & Tienda, 1998; Vowell & May, 2000). In this discussion, I explain more how both the protective and restrictive factors operate in collective expectations.…”
Section: Discussionmentioning
confidence: 99%
“…The statements used a Likert-type format designed to assess adolescents' attitudes and perceptions of crime. Several questions were also included to assess demographic character-istics (e.g., race, gender, income, parent's occupation), along with a number of questions used frequently in other studies (Vowell and May 2000 ;May 1997May , 1999) that examined the adolescent's participation in deviant activities. Students required approximately 45 minutes to complete the surveys.…”
Section: Methodsmentioning
confidence: 99%
“…Although certain previous studies have observed a significant relationship between perceived opportunity and delinquency (for reviews, see Burton & Cullen, 1992;Vowell & May, 2000), we know little about the role of perceived opportunity in the development of code-related beliefs in particular and the extent to which code-related beliefs mediate the relationship between perceived opportunity and violent behavior. Nor do we have an adequate understanding of the influence of victimization, the threat of victimization, and other factors related to environmental pressures or demands.…”
Section: Drawing On Anderson's Insights To Extend Youth Violence Resementioning
confidence: 96%